PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA BANJARBENDO KECAMATAN SIDOARJO KABUPATEN SIDOARJO - Renanda Ayu; Hendra Sukmana (Journal Publicuho, 2023)
This research aims to determine and analyze Community Participation in Development in Banjarbendo Village, Sidoarjo District, Sidoarjo Regency. The research method used is descriptive qualitative research. The data collection techniques used were interviews, observation, and literature study. The research results show that participation in decision-making is not optimal because the proposals approved with a priority scale are only 10 types of development and interruptions always occur during meetings. Participation in the implementation of physical and non-physical development is hampered by a lack of community participation. Community participation in taking benefits has not contributed much to residents. Participation in the evaluation means that the people of Banjarbendo Village always submit evaluations in the form of criticism.